Non-destructive DNA extraction for recovering mitochondrial genomes from museum grasshopper specimens - Hao Tang; Jiayi Zou; Keyao Zhang; Huateng Huang (PLoS ONE, 2026)
Museum collections of grasshoppers contain valuable genetic data for evolutionary, ecological, and systematic studies, but destructive sampling and complex molecular techniques often limit their use. This study presents a simple, non-destructive DNA extraction protocol designed for dried grasshopper specimens, effectively balancing DNA yield with morphological preservation. We tested this method on specimens aged 6–43 years, exploring various lysis conditions to optimize DNA recovery while maintaining specimen integrity. The protocol successfully extracted sufficient DNA to assemble mitochondrial genomes for most samples using cost-effective low-coverage shotgun sequencing. DNA from younger specimens produced the best results, while older samples (over 40 years) showed some challenges, though post-collection damage did not significantly affect mitochondrial sequence assembly. Additionally, we provide practical bioinformatics recommendations for processing short reads from dried specimens. Requiring minimal molecular expertise and relying on standard sequencing services, this accessible method is well-suited for widespread adoption. By unlocking genetic insights from museum collections, it offers new opportunities to deepen our understanding of grasshopper evolution and ecological dynamics.